2017
DOI: 10.1515/jomb-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Association of Myeloperoxidase and the Atherogenic Index of Plasma in Children with End-Stage Renal Disease

Abstract: SummaryBackgroundThe aim of this study was to explore oxidative stress status, especially the enzyme myeloperoxidase in children with end-stage renal disease. Also, we investigated possible associations between the atherogenic index of plasma and these parameters.MethodsLipid status parameters, oxidative stress status parameters, and myeloperoxidase concentration were measured in the sera of 20 children in the last stage of chronic renal disease (ESRD) and 35 healthy children of matching age and sex. The Ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(42 reference statements)
0
5
0
1
Order By: Relevance
“…Currently, myeloperoxidase activity is considered as an independent indicator of inflammation and oxidative stress. This enzyme in leukocyte usually has the capacity to catalyze the hydrogen peroxide [ 24 ]. Clinically, myeloperoxidase activity has been used to predict inflammation and oxidative stress in renal failure [ 25 ], myocardial infarction [ 26 ], inflammatory vascular disease [ 27 ], and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, myeloperoxidase activity is considered as an independent indicator of inflammation and oxidative stress. This enzyme in leukocyte usually has the capacity to catalyze the hydrogen peroxide [ 24 ]. Clinically, myeloperoxidase activity has been used to predict inflammation and oxidative stress in renal failure [ 25 ], myocardial infarction [ 26 ], inflammatory vascular disease [ 27 ], and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Rutin as a phytochemical may open another therapeutic window in the treatment of XOD‐associated hypertension and cardiorenal dysfunction through its antioxidant property. The increased in serum levels of AOPP and MPO in NaF alone treated rats are also pointers to oxidative stress, inflammation, end‐stage renal disease, arteriosclerosis, and endothelial dysfunction as previously desscribed . Increased in the level of AOPP and activity of MPO has been shown to increase the oxidation of LDL to oxidized low‐density lipoprotein cholesterol (ox‐LDL) as a curser factor in the pathogenesis of arteriosclerosis with decreasing myocardial contractility .…”
Section: Discussionmentioning
confidence: 78%
“…In the 1980s, neopterin levels were a popular predictor of postoperative acute rejection reactions and viral infections in transplantation studies, but have since been »forgotten« as a biomarker (15). A significant abnormality has been found in the pteridine metabolism in patients with CKF in subsequent studies (10).…”
Section: Discussionmentioning
confidence: 85%
“…Although it is suggested in the aforementioned study that neopterin is not specific in the evaluation of disease prognosis, there are many studies suggesting that neopterin is useful as a biological marker when following-up the clinical course of the disease or assess prognosis. Several studies have reported that serum or urine neopterin levels increase in cases of idiopathic or primary nephrotic syndrome, chronic and acute glomerulonephritis, and different stages of chronic kidney disease (7, 8, 9, 10), and it has been also shown that neopterin levels are elevated in patients with end-stage renal disease (ESRD) undergoing longterm hemodialysis, and that this increase is correlated with the duration of hemodialysis. Also in the aforementioned study it is demonstrated that in cases of human immunodeficiency virus (HIV) infection, the risk of developing acquired immune deficiency syndrome (AIDS) may increase in patients undergoing dialysis for more than one year.…”
Section: Introductionmentioning
confidence: 99%